Calcareous Nannofossils from the Shiranish Formation at Bekhaer anticline, Dhouk area, Northern Iraq - Omar A. Al-Badrani; Mahfoud A. Al-Hadeedy; Ibrahim Y. Al-Shareefi (Tikrit Journal of Pure Science)
Calcareous nannofossils are examined up on the Shiranish Formation from the Bekhaer anticline in Northern Iraq. The study area includes about 55 meters to find calcareous nannofossils assemblages, from which (36) species have identified.